Ethosomes for Curcumin and Piperine Cutaneous Delivery to Prevent Environmental-Stressor-Induced Skin Damage - Francesca Ferrara; Agnese Bondi; Walter Pula; Catia Contado; Anna Baldisserotto; Stefano Manfredini; Paola Boldrini; Maddalena Sguizzato; Leda Montesi; Mascia Benedusi; Giuseppe Valacchi; Elisabetta Esposito (MDPI AG, 2024)
Diesel particulate matter is one of the most dangerous environmental stressors affecting human health. Many plant-derived compounds with antioxidant and anti-inflammatory properties have been proposed to protect the skin from pollution damage. Curcumin (CUR) has a plethora of pharmacological activities, including anticancer, antimicrobial, anti-inflammatory and antioxidant. However, it has low bioavailability due to its difficult absorption and rapid metabolism and elimination. CUR encapsulation in nanotechnological systems and its combination with biopotentiators such as piperine (PIP) can improve its pharmacokinetics, stability and activity. In this study, ethosomes (ETs) were investigated for CUR and PIP delivery to protect the skin from damage induced by diesel particulate matter. ETs were produced by different strategies and characterized for their size distribution by photon correlation spectroscopy, for their morphology by transmission electron microscopy, and for their drug encapsulation efficiency by high-performance liquid chromatography. Franz cells enabled us to evaluate in vitro the drug diffusion from ETs. The results highlighted that ETs can promote the skin permeation of curcumin. The studies carried out on their antioxidant activity demonstrated an increase in the antioxidant power of CUR using a combination of CUR and PIP separately loaded in ETs, suggesting their possible application for the prevention of skin damage due to exogenous stressors. Ex vivo studies on human skin explants have shown the suitability of drug-loaded ETs to prevent the structural damage to the skin induced by diesel engine exhaust exposure.